Anti-adhesive composition for unvulcanized rubber and its use
The anti-adhesive composition for unvulcanized rubber, comprising silicate and a specific surfactant ratio, addresses sedimentation and adhesion issues, improving dispersibility and adhesion prevention to enhance rubber product quality and productivity.
Patent Information
- Application Number
- JP2021008352
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-02-28
- Filing Date
- 2021-01-22
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2041-01-22
AI Technical Summary
Existing anti-adhesive agents for unvulcanized rubber suffer from sedimentation issues and inadequate adhesion prevention, leading to environmental deterioration and reduced productivity due to sediment generation and uneven coating.
An anti-adhesive composition containing silicate, iron oxide or iron sulfide, and a specific ratio of anionic and nonionic surfactants, with a weight ratio of iron compounds limited to 10% or less, ensures excellent dispersibility and adhesion prevention.
The composition improves workability and reduces defects in rubber products by providing superior dispersibility and adhesion prevention, enhancing productivity and environmental safety.
Smart Images

Figure 0007603459000001 
Figure 0007603459000002 
Figure 0007603459000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an anti-adhesive composition for unvulcanized rubber and its use. [Background technology]
[0002] In the production and processing of rubber products, unvulcanized rubber is sometimes stored in piles until it is moved to the next process such as molding or vulcanization. In this case, anti-adhesion agents (anti-adhesion agents) are used to prevent the rubber from sticking together. The anti-adhesive agents that are widely used are those that contain inorganic powders and surfactants as their main components, and are generally applied to the rubber surface in the form of an aqueous dispersion and then dried. The application method is to spray the aqueous dispersion or to immerse the rubber surface in the aqueous dispersion. However, when using these aqueous dispersions of inorganic powders, sediments are generated, which can cause a deterioration of the working environment and a decrease in productivity. If a large amount of sediment is generated, cleaning of the equipment in use is required, and the spray blockage and uneven concentration of the dispersion liquid can hinder uniform application. For these reasons, there is a demand for the development of an anti-adhesive agent that produces less sediment and has excellent anti-adhesive performance.
[0003] Although various adhesion inhibitors have been developed so far, there has been no adhesion inhibitor that solves the above problems and provides sufficient adhesion prevention properties. Patent Document 1 discloses an anti-adhesive agent that contains bentonite containing a specific amount of montmorillonite, which is a water-swellable inorganic powder, and a surfactant containing an anionic surfactant and a nonionic surfactant in a specific ratio as essential components. By making the blending ratio of the nonionic surfactant higher than that of the anionic surfactant, the adhesion of the anti-adhesive agent to the rubber surface is improved, thereby improving the anti-adhesive properties. However, when the dispersion liquid is in a low concentration, the dispersing effect of the anionic surfactant on the inorganic powder is significantly reduced, and the agent is prone to settling. Patent Document 2 discloses a method of preventing adhesion by applying to the rubber surface a composition in which fatty acid soap and metal soap with limited carbon numbers and metal ions and a specific surfactant are dispersed in water. Since no inorganic powder is used, there is no problem with sedimentation, but in order to exert a sufficient adhesion prevention effect, it is necessary to use it at a high concentration, which has the problem of deteriorating the physical properties of the vulcanized rubber, and therefore the method of use is limited and it is not versatile. As described above, various anti-adhesion agents have been developed, but none of them are capable of suppressing the precipitation of inorganic powder and providing sufficient anti-adhesion properties. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2013-213202 A [Patent Document 2] Japanese Patent Application Publication No. 49-18780 Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide an adhesion-preventive composition for unvulcanized rubber that is excellent in both dispersibility and adhesion prevention, and a method for producing unvulcanized rubber that has been treated with an adhesion prevention agent using the adhesion-preventive composition for unvulcanized rubber. [Means for solving the problem]
[0006] As a result of intensive research into solving the above-mentioned problems, the present inventors have found that the above-mentioned problems can be solved by an anti-adhesive composition in which the weight ratio of the iron oxide and the iron sulfide to the total of silicate, iron oxide, and iron sulfide is within a specific range, and the anionic surfactant (A) and the nonionic surfactant (B) are contained in a specific ratio.
[0007] That is, the adhesion-preventive composition for unvulcanized rubber of the present invention is an adhesion-preventive composition for unvulcanized rubber containing an inorganic component and a surfactant, the inorganic component essentially containing a silicate and at least one selected from iron oxide and iron sulfide, the total weight ratio of the iron oxide and the iron sulfide to the total of the silicate, the iron oxide and the iron sulfide is 10% by weight or less, the surfactant contains an anionic surfactant (A) and a nonionic surfactant (B), and the weight ratio (A / B), expressed as the weight of (A) / the weight of (B), is 1 to 20.
[0008] It is preferred that the composition further contains a carbonate and / or a metal soap. The anionic surfactant (A) preferably comprises a fatty acid soap.
[0009] The method for producing adhesion-preventively treated unvulcanized rubber of the present invention includes a treatment step of adhering the above-mentioned adhesion-preventive composition for unvulcanized rubber to the surface of molded unvulcanized rubber. Effect of the Invention
[0010] The anti-adhesive composition for unvulcanized rubber of the present invention is excellent in dispersibility and anti-adhesiveness. Furthermore, in the method for producing unvulcanized rubber of the present invention, since the anti-adhesive composition for unvulcanized rubber of the present invention is used, the workability is improved due to good dispersibility and anti-adhesiveness, and defects in rubber products can be reduced. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] [Anti-adhesive composition for unvulcanized rubber] The adhesion-preventive composition for unvulcanized rubber of the present invention is an adhesion-preventive composition for unvulcanized rubber which contains an inorganic component essentially consisting of a silicate, and a surfactant. Each component will be described in detail below.
[0012] [Inorganic components] The inorganic component is a component of a material that forms a coating on the surface of unvulcanized rubber and exhibits adhesion prevention properties. The adhesion inhibitor composition for unvulcanized rubber of the present invention contains silicate as an essential inorganic component. Silicates generally have a structure formed by linking silicate tetrahedra, each of which is formed by inserting one silicon atom into the gap in the center of a triangular pyramid formed by four oxygen atoms. Silicates are further classified into nesosilicates, solosilicates, cyclosilicates, inosilicates, phyllosilicates, tectosilicates, etc., depending on the linking method of the silicate tetrahedra, and the adhesion inhibitor for unvulcanized rubber of the present invention may use one or more of these silicates in combination.
[0013] Nesosilicates are classified as independent interlocking silicates (SiO4) 4- The basic composition is a structure represented by the chemical formula: The nesosilicate is not particularly limited, but examples thereof include olivine such as forsterite, fayalite, and manganese olivine, humite, garnets such as pyrope, almandine, spessartine, grossular, andradite, and uvarovite, and gadolinites such as datolite and sillimanite, and the like, and these may be used alone or in combination of two or more. Solosilicates are classified as complex interlocking silicates (Si2O7) 6- and (SiO 16 ) 12- The basic composition is at least one selected from the structures represented by the chemical formula: The nesosilicate is not particularly limited, but examples thereof include epidote such as zoisite and clinozoisite, melilite such as akermanite and gehlenite, and pumpellyite such as vesuvianite, and the like, and these may be used alone or in combination of two or more.
[0014] Cyclosilicates are classified as ring-linked silicates (Si3O9). 6- , (SiO 12 ) 8- , (SiO 18 ) 12- The basic composition is a structure represented by the chemical formula: The nesosilicate is not particularly limited, but examples thereof include benitoite, beryl, tourmaline such as ferroelectric, magnesite, and sphaerolite, and osumilite, and these may be used alone or in combination of two or more. Inosilicates are classified as single-chain silicates (Si2O6) 4-, (Si3O9) 6- , (SiO 11 ) 6- , (SiO 15 ) 10- , (SiO 21 ) 14- The basic composition is a structure represented by the chemical formula: The inosilicate is not particularly limited, but examples thereof include pyroxenes such as diopside, clinoenstatite, enstatite, acmite, and spodumene, and amphibole such as anthophyllite, tremolite, glaucophane, and rhodonite, and these may be used alone or in combination of two or more.
[0015] Phyllosilicates are classified as layer-connected silicates and have a basic structure represented by the chemical formula SiO2. Examples of phyllosilicates include, but are not limited to, smectites such as montmorillonite, beidellite, nontronite, saponite, hectorite, sauconite, and stevensite; vermiculites such as di-vermiculite and tri-vermiculite; kaolinites such as halloysite, kaolin, endelite, dickite, nacrite, and chrysotile; talc; mica such as tetrasilylic mica; pyrophyllite; margarite; clintonite; mica minerals such as muscovite, biotite, phlogopite, synthetic mica, and fluorine mica; jamonites such as paragolite, phlogopite, lepidolite, and antigorite; chlorites such as dompatite, sudolite, cookite, clinochlore, chamosite, chlorite, and nanite; and piolite-palygorskite such as sepiolite and palygorskite. These may be used alone or in combination of two or more. Tectosilicates are classified as silicates with a network structure, and have a basic structure represented by the chemical formula SiO2. There are no particular limitations on the tectosilicates, and examples thereof include feldspars such as sanidine, albite, anorthite, and nepheline; zeolites such as leucite, scosite, and heulandite; and stilts, and these may be used alone or in combination of two or more.
[0016] The silicate contained in the inorganic component used in the present invention preferably contains a phyllosilicate, which can form a coating film with good water dispersibility and excellent adhesion prevention. Among them, it is preferable that the phyllosilicate is at least one selected from smectite, kaolinite, talc, and mica, since it forms a coating film with excellent adhesion prevention. When smectite comes into contact with water, the water molecules are successively hydrated with the exchangeable cations between the layers, causing the smectite to swell, and therefore it can be effectively dispersed in water. Therefore, it is more preferable that the phyllosilicate is smectite, since it has excellent dispersibility when mixed with water and improves the film forming properties. Among smectites, montmorillonite is preferable because it has particularly remarkable water swelling properties.
[0017] Montmorillonite is a dioctahedral hydrous layered silicate mineral that contains sodium, calcium, potassium, magnesium, hydrogen ions, etc. as exchangeable cations. These cations are easily exchangeable and also have the property of absorbing water easily. When the exchangeable cation is sodium ion, it easily absorbs water molecules due to hydration force, and the layer spacing increases, causing significant swelling. Generally, a layered clay mineral containing montmorillonite as a main component is called bentonite. Bentonite is an example of an inorganic component, and can be easily adsorbed to the surface of unvulcanized rubber to form a coating. The bentonite coating has excellent adhesion prevention and slip properties, so it is more preferable that the silicate in the adhesion inhibitor composition for unvulcanized rubber of the present invention contains bentonite as an essential component. In addition, when the bentonite contains sodium bentonite with high purity, the effect of water swelling is remarkable, which is particularly preferable.
[0018] The amount of silicate contained in the anti-adhesive composition for unvulcanized rubber of the present invention is not particularly limited, but is preferably 30 to 90 parts by weight, more preferably 32.5 to 87.5 parts by weight, even more preferably 35 to 85 parts by weight, and particularly preferably 37.5 to 82.5 parts by weight, when the total amount of the inorganic component and the surfactant is 100 parts by weight. If the silicate content is 30 parts by weight or more, the adhesion prevention tends to be improved, and if it is 90 parts by weight or less, the dispersibility tends to be improved.
[0019] The inorganic component essentially contains at least one selected from iron oxide and iron sulfide in addition to the silicate. The total weight ratio of iron oxide and iron sulfide to the total of silicate, iron oxide and iron sulfide is 10% by weight or less. Silicate may be present together with a trace amount of iron compound. However, since iron compounds have a larger specific gravity than silicate and carbonate, if the weight ratio of iron compounds in silicate exceeds 10% by weight, sedimentation occurs, which causes deterioration of productivity and deterioration of anti-adhesion properties. The iron compound in the present invention is at least one selected from iron oxide and iron sulfide, and may contain both. The total weight ratio of iron oxide and iron sulfide to the total of silicate, iron oxide and iron sulfide is preferably 9% by weight or less, more preferably 8% by weight or less, even more preferably 7% by weight or less, and particularly preferably 6% by weight or less. On the other hand, the lower limit of the total weight ratio of iron oxide and iron sulfide to the total of silicate, iron oxide and iron sulfide is not particularly limited, but is preferably (1) more than 0% by weight, (2) 0.05% by weight, (3) 0.1% by weight, (4) 0.3% by weight, (5) 0.6% by weight, (6) 0.7% by weight, (7) 0.8% by weight, (8) 0.9% by weight, and (9) 1% by weight in that order (the larger the value in parentheses, the more preferable it is).
[0020] As a method for adjusting the weight ratio of iron oxide and iron sulfide to the total of silicate, iron oxide, and iron sulfide, a commercially available silicate containing coexisting iron compounds in an amount of 10% by weight or less can be obtained, but a silicate composition containing an iron compound may be subjected to a process such as centrifugation or centrifugal separation, or an iron compound may be mixed therein.
[0021] [Method of Analyzing Weight Percentage of Iron Compounds] The weight percentage of iron compounds present together with silicates is measured by powder X-ray diffraction. When the measured value is below the detection limit, it is recorded as 0% by weight.
[0022] The inorganic component may contain an inorganic substance other than silicate, iron oxide, and iron sulfide. The inorganic substance other than silicate, iron oxide, and iron sulfide is not particularly limited, and examples thereof include carbonates such as calcium carbonate, sodium carbonate, and magnesium carbonate; sulfates such as calcium sulfate and barium sulfate; metal oxides such as amorphous silica, alumina, magnesium oxide, antimony trioxide, titanium oxide, and white carbon; metal hydroxides such as aluminum hydroxide and magnesium hydroxide; red iron oxide; carbon black; and graphite. Among these inorganic substances other than silicates, iron oxides and iron sulfides, carbonates are preferred from the viewpoint of adhesion prevention of unvulcanized rubber, and at least one selected from calcium carbonate, sodium carbonate and magnesium carbonate is more preferred.
[0023] The average particle size of the inorganic component is not particularly limited, but taking into consideration the adhesion to unvulcanized rubber, etc., it is preferably 0.1 to 200 μm, more preferably 0.1 to 100 μm, even more preferably 0.1 to 50 μm, particularly preferably 0.1 to 40 μm, and most preferably 0.1 to 30 μm.
[0024] [Surfactant] The surfactant is an essential component of the present invention, and is a component that assists in the dispersion of the adhesion-preventive composition and assists in the "wetting" of the unvulcanized rubber. By including a surfactant in the adhesion-preventive composition for unvulcanized rubber of the present invention, the dispersibility of the inorganic components is improved, suppressing sedimentation, and the wettability of the unvulcanized rubber is improved, allowing a more uniform coating to be formed on the surface of the unvulcanized rubber.
[0025] The surfactant used in the present invention essentially contains an anionic surfactant and a nonionic surfactant. The anionic surfactant improves the dispersibility of the anti-adhesive composition, and the nonionic surfactant improves the adhesion of the anti-adhesive composition to rubber. Therefore, both the anionic surfactant and the nonionic surfactant are essential.
[0026] An important point in the present invention is the correlation between the weight ratio of iron oxide and iron sulfide to the total of silicate, iron oxide and iron sulfide, and the weight ratio (A / B) represented by the anionic surfactant (A) and the nonionic surfactant (B). In other words, it was found that the substance that inhibits the stability of the anti-adhesive composition is an iron compound, and it was discovered that when the iron compound is at a specific value and an anionic surfactant (A) and a nonionic surfactant (B) are blended in a specific ratio, the iron compound can be adequately dispersed.
[0027] That is, to satisfy both dispersibility and adhesion, the weight ratio (A / B) of the anionic surfactant (A) to the nonionic surfactant (B) must be in the range of 1 to 20. If A / B is less than 1, dispersibility decreases and sediment increases. On the other hand, if A / B exceeds 20, adhesion decreases. A / B is preferably 1.2 to 18, more preferably 1.4 to 16, and even more preferably 1.6 to 14.
[0028] The anionic surfactant and the nonionic surfactant are not particularly limited, and one or more kinds may be contained. Examples of anionic surfactants include fatty acid soaps such as potassium caprate, sodium caprate, sodium laurate, potassium laurate, sodium palmitate, potassium plumitate, potassium stearate, sodium stearate, sodium palm kernel oil fatty acid, potassium palm kernel oil fatty acid, potassium palm stearate, sodium palm stearate, sodium coconut oil fatty acid, potassium coconut oil fatty acid, sodium tallow fatty acid, and potassium tallow fatty acid; alkyl sulfates such as sodium lauryl sulfate, ammonium lauryl sulfate, sodium stearyl sulfate, and sodium cetyl sulfate; polyoxyalkylene alkyl ether acetates such as sodium polyoxyethylene tridecyl ether acetate; alkyl benzene sulfonates such as sodium dodecyl benzene sulfonate; and polyoxyalkylene alkyl ether sulfates. long-chain sulfosuccinates such as sodium dioctyl sulfosuccinate, sodium 2-ethylhexyl sulfosuccinate, etc.; N-acyl sarcosine salts such as sodium oleoyl sarcosine, sodium lauroyl sarcosine, etc.; higher fatty acid amide sulfonates such as sodium stearoyl methyl taurine, sodium lauroyl methyl taurine, sodium myristoyl methyl taurine, sodium palmitoyl methyl taurine, etc.; alkyl phosphates such as sodium monostearyl phosphate; polyoxyalkylene alkyl ether phosphate salts such as sodium polyoxyethylene oleyl ether phosphate, sodium polyoxyethylene stearyl ether phosphate, etc.; long-chain N-acyl glutamate salts such as sodium monosodium lauroyl glutamate, disodium N-stearoyl-L-glutamate, etc., and these may be used alone or in combination of two or more.
[0029] Examples of the nonionic surfactant include decyl ether to which 3 moles of polyoxyethylene have been added, decyl ether to which 3 moles of polyoxyethylene have been added and 1 mole of polyoxypropylene have been added, decyl ether to which 5 moles of polyoxyethylene have been added, decyl ether to which 7 moles of polyoxyethylene have been added, isodecyl ether to which 3 moles of polyoxyethylene have been added, isodecyl ether to which 3 moles of polyoxyethylene have been added and 1 mole of polyoxypropylene have been added, isodecyl ether to which 5 moles of polyoxyethylene have been added, isodecyl ether to which 7 moles of polyoxyethylene have been added, lauryl ether to which 3 moles of polyoxyethylene have been added and 1 mole of polyoxypropylene have been added, lauryl ether to which 5 moles of polyoxyethylene have been added, lauryl ether to which 7 moles of polyoxyethylene have been added, tridecyl ether to which 3 moles of polyoxyethylene have been added, tridecyl ether to which 3 moles of polyoxyethylene have been added and 1 mole of polyoxypropylene have been added, tridecyl ether to which 5 moles of polyoxyethylene have been added, tridecyl ether to which 7 moles of polyoxyethylene have been added, polyoxyethylene polyoxyalkylene alkyl ethers such as isotridecyl ether of 3 moles of polyoxyethylene added, isotridecyl ether of 3 moles of polyoxyethylene and 1 mole of polyoxypropylene added, isotridecyl ether of 5 moles of polyoxyethylene added, isotridecyl ether of 7 moles of polyoxyethylene added, myristyl ether of 3 moles of polyoxyethylene added, myristyl ether of 3 moles of polyoxyethylene and 1 mole of polyoxypropylene added, myristyl ether of 5 moles of polyoxyethylene added, myristyl ether of 7 moles of polyoxyethylene added, cetyl ether of 3 moles of polyoxyethylene added, cetyl ether of 3 moles of polyoxyethylene and 1 mole of polyoxypropylene added, cetyl ether of 5 moles of polyoxyethylene added, and cetyl ether of 7 moles of polyoxyethylene added; polyoxyalkylene alkyl phenyl ethers such as polyoxyethylene nonylphenyl ether and polyoxyethylene octylphenyl ether; polyoxyalkylene fatty acid esters such as polyoxyethylene monolaurate and polyoxyethylene monooleate;Examples of the polyoxyalkylene sorbitan fatty acid esters include polyoxyethylene sorbitan monostearate and polyoxyethylene sorbitan monooleate; polyoxyalkylene alkylamines; fatty acid alkanolamides; polyoxyalkylene fatty acid amides; polyoxyalkylene hydrogenated castor oil; polyoxyalkylene sorbitol fatty acid esters; polyglycerin fatty acid esters; alkyl glycerin ethers; polyoxyalkylene cholesteryl ethers; alkyl polyglucosides; sucrose fatty acid esters; and oxyethylene-oxypropylene block polymers, and these may be used alone or in combination of two or more.
[0030] The amount of the surfactant contained in the anti-adhesive composition for unvulcanized rubber of the present invention is not particularly limited, but is preferably 1 to 40 parts by weight, more preferably 2 to 35 parts by weight, even more preferably 3 to 30 parts by weight, and particularly preferably 4 to 25 parts by weight, when the total amount of the inorganic component and the surfactant is 100 parts by weight. If the content of the surfactant is 1 part by weight or more, dispersibility tends to be improved, and if it is 40 parts by weight or less, adhesion prevention tends to be improved.
[0031] The adhesion inhibitor composition for unvulcanized rubber of the present invention may further contain the following components in addition to the components explained above.
[0032] [Metal soap] Metal soap is a component that adheres to the surface of unvulcanized rubber and can reduce friction between unvulcanized rubbers. Examples of metal soap include magnesium laurate, calcium laurate, zinc laurate, magnesium myristate, calcium myristate, zinc myristate, magnesium palmitate, calcium palmitate, zinc palmitate, magnesium stearate, calcium stearate, zinc stearate, aluminum trioctadecanoate, aluminum dioctadecanoate, aluminum monooctadecanoate, calcium octadecanoate, zinc octadecanoate, magnesium octadecanoate, barium octadecanoate, etc., and one or more of them may be used in combination. As the metal soap, at least one selected from magnesium stearate, calcium stearate, and zinc stearate is preferred because it is highly effective in reducing friction between unvulcanized rubbers.
[0033] Furthermore, it is preferable for the adhesion preventive composition for unvulcanized rubber of the present invention to contain a carbonate and / or a metal soap in order to obtain the effects of the present invention. When the anti-adhesive composition for unvulcanized rubber of the present invention contains a carbonate and / or a metal soap, the total content of the carbonate and the metal soap is not particularly limited, but is preferably 1 to 40 parts by weight, more preferably 2 to 35 parts by weight, even more preferably 3 to 30 parts by weight, and most preferably 4 to 25 parts by weight, when the total amount of the inorganic component and the surfactant is 100 parts by weight. When the total content of the carbonate and the metal soap is 1 part by weight or more, dispersibility tends to be improved, and when it is 40 parts by weight or less, adhesion prevention tends to be improved.
[0034] [Water-soluble polymer] The water-soluble polymer is a component that can impart viscosity to the adhesion-preventive composition for unvulcanized rubber and improve adhesion to the surface of unvulcanized rubber. In particular, when the composition for unvulcanized rubber is in the form of an aqueous dispersion as described below, the effect can be further enhanced. Examples of water-soluble polymers include starches such as oxidized starch, starch acetate, starch phosphate, carboxymethyl starch, carboxyethyl starch, hydroxyethyl starch, cationic starch, cyanoethylated starch, and dialdehyde starch; mannan; alginic acids such as alginic acid, sodium alginate, propylene glycol alginate, triethanolamine alginate, and ammonium alginate; methylcellulose, ethylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, hydroxypropylmethylcellulose, hydroxyethylmethylcellulose, and hydroxypropylmethylcellulose; Examples of water-soluble polymers include cellulose ethers such as ethyl cellulose, hydroxyethyl ethyl cellulose, and carboxymethyl cellulose; natural gums such as taracant gum, gum arabic, guar gum, xanthan gum, British gum, glucomannan, gellan gum, tara gum, locust bean gum, and carrageenan; sodium polyacrylate; polyvinyl alcohol; polyethylene glycol; polyethylene oxide; water-soluble acrylic resins; water-soluble urethane resins; water-soluble melamine resins; water-soluble epoxy resins; water-soluble butadiene resins; and water-soluble phenolic resins, and these may be used alone or in combination of two or more.
[0035] [Polyhydric alcohol] Polyhydric alcohol is a component that adheres to the surface of unvulcanized rubber and can impart lubricity to unvulcanized rubber particles, thereby reducing friction between unvulcanized rubber particles. Examples of polyhydric alcohols include glycerin, 1,3-butanediol, propylene glycol, dipropylene glycol, pentylene glycol, neopentyl glycol, hexylene glycol, polyethylene glycol, erythritol, pentaerythritol, dipentaerythritol, trimethylolethane, trimethylolpropane, ditrimethylolpropane, xylitol, sorbitol, mannitol, maltitol, maltotriose, glucose, sucrose, fructose, and maltose, and one or more of these may be used in combination.
[0036] [Antifoaming agent] Examples of the defoaming agent include silicone-based defoaming agents such as polymethylsiloxane and polyether-modified silicone; oil-based defoaming agents such as castor oil, sesame oil, linseed oil, and animal and vegetable oils; fatty acid-based defoaming agents such as stearic acid, oleic acid, and palmitic acid; fatty acid ester-based defoaming agents such as isoamyl stearate, distearyl succinate, ethylene glycol distearate, and butyl stearate; and aryl ester-based defoaming agents such as polyoxyalkylene monohydric alcohol di-t-amylphenoxyethanol, 3-heptanol, and 2-ethylhexanol. Examples of such defoamers include alcohol-based defoamers; ether-based defoamers such as di-t-amylphenoxyethanol, 3-heptyl cellosolve, nonyl cellosolve, and 3-heptyl carbitol; phosphate-based defoamers such as tributyl phosphate and tris(butoxyethyl) phosphate; amine-based defoamers such as diamylamine; amide-based defoamers such as polyalkylene amide and acylate polyamine; sulfate-based defoamers such as sodium lauryl sulfate; polyoxyalkylene-based defoamers; and mineral oils, and these may be used alone or in combination of two or more.
[0037] [Preservatives] Examples of preservatives include thiazoles such as thiazole and 2-mercaptothiazole; thiocyanates such as methylene bisthiocyanate and ammonium thiocyanate; sulfimides such as o-benzoic sulfimide and phenylmercuric-o-benzoic sulfimide; alkyl dialkyl thiocarbamates such as methyl dimethyl thiocarbamate and ethyl diethyl dithiocarbamate; thiuram sulfides such as tetramethyl thiraum sulfide and tetraethyl thiraum sulfide; thiuram disulfides such as tetramethyl thiraum disulfide and tetraethyl thiraum disulfide; dithiocarbamates such as ferric diethyl dithiocarbamate and lead dimethyl dithiocarbamate; sulfamides such as o-toluenesulfonamide and benzenesulfonanilide; 1-aminonaphthyl-4-sulfonic acid, 1-amino phenols and alkali metal salts thereof such as pentachlorophenol and o-phenylphenol; chloroquinones such as tetrachloro-p-benzoquinone and 2,3-dichloro-1,4-naphthoquinone; nitro group-containing compounds such as dinitrocaprylphenylcrotonate and dinitro-o-cresol; triazines such as 1,3,5-trihydroxyethylhexahydro-1,3,5-triazine and 1,3,5-triethylhexahydro-1,3,5-triazine; organic mercury compounds such as phenylmercuric phthalate and o-hydroxyphenylmercuric chloride; amines such as p-aminoazobenzene and diphenylamine; amides such as cinnamanilide; and iodine-containing compounds such as 1,3-diiodo-2-propanol. These may be used alone or in combination of two or more.
[0038] 〔water〕 The anti-adhesive composition for unvulcanized rubber of the present invention may contain water. It is preferable that the anti-adhesive composition for unvulcanized rubber contains water from the viewpoint of handling properties. The water may be any of tap water, ion-exchanged water, distilled water, etc., and is not particularly limited, but ion-exchanged water and distilled water are preferred. From the viewpoint of quality control, soft water is preferred because its hardness can be adjusted. When the adhesion-preventive composition for unvulcanized rubber of the present invention contains water, the adhesion-preventive composition for unvulcanized rubber may be in the form of an aqueous dispersion in which components other than water are dispersed or dissolved in water.
[0039] When the adhesion-preventive composition for unvulcanized rubber of the present invention is in the form of an aqueous dispersion, the weight ratio of water in the adhesion-preventive composition for unvulcanized rubber is not particularly limited, but is preferably 90 to 99.99% by weight, more preferably 92.5 to 99.95% by weight, and even more preferably 95 to 99.5% by weight. When the weight ratio of water is 90% by weight or more, the drying property tends to be improved, and when it is 99.9% by weight or less, the adhesion prevention property tends to be improved.
[0040] [Method for producing anti-adhesive agent for unvulcanized rubber] In the production method of the adhesion-preventive composition for unvulcanized rubber of the present invention, there is no particular limitation on the mixing order, mixing equipment to be used, etc., as long as it includes a step of mixing an inorganic component, a surfactant, and, if necessary, other components, etc. The adhesion-preventive composition for unvulcanized rubber can be produced, for example, by sequentially adding each component to a mixer such as a ribbon mixer or a vertical screw mixer and mixing them.
[0041] [Method for producing anti-adhesive treated unvulcanized rubber] The method for producing an adhesion-preventive treated unvulcanized rubber of the present invention includes a treatment step of adhering the adhesion-preventive composition for unvulcanized rubber to the surface of the unvulcanized rubber. Here, the unvulcanized rubber is preferably one that has been molded. In the treatment step, a wet method, that is, a method using the above-mentioned anti-adhesive composition for unvulcanized rubber in the form of an aqueous dispersion, is preferred.
[0042] When the treatment step is carried out by a wet method, examples of the method include spraying the anti-adhesive composition for unvulcanized rubber in the form of an aqueous dispersion, spraying the rubber with a thin stream, and immersing the rubber in an aqueous dispersion. The method of immersing in an aqueous dispersion is preferred because it allows the adhesion inhibitor composition for unvulcanized rubber to be uniformly adhered. The unvulcanized rubber used in the production method of the present invention is usually in a heated state at 100 to 180°C, and the unvulcanized rubber can be cooled by immersing in an aqueous dispersion. The temperature of the aqueous dispersion is not particularly limited, but is preferably 0 to 60°C. Next, a step of drying the unvulcanized rubber after the aqueous dispersion is applied may be carried out. The drying method is not particularly limited, but a method of forcibly drying by blowing hot air with a hot air blower or a blow heater is preferable because it is inexpensive.
[0043] In the treatment step, a dry method, that is, a method using an anti-adhesive composition for unvulcanized rubber that does not contain water, may be used. The anti-adhesion treated unvulcanized rubber produced in this manner can be prevented from sticking to each other when it is stacked and stored until it is moved to the next process. EXAMPLES
[0044] The present invention will be specifically described below with reference to examples and comparative examples. The present invention is not limited to these examples. The physical properties in the examples and comparative examples were evaluated as follows. Examples 1, 19 to 21, and 23 are considered as reference examples.
[0045] [Adhesion resistance] An NR / BR test piece (natural rubber / butadiene rubber; thickness 0.5 cm × length 5 cm × width 3 cm) heated to 100°C was immersed in an aqueous dispersion of an anti-adhesive composition for unvulcanized rubber (weight ratio of water was 98.5 wt%) and then immediately removed. Two immersed rubber test pieces were prepared, air-dried, stacked, and subjected to a load of 1000 kg / m 2 A load of 10 ... Peel resistance of 1N / cm or less: Very good adhesion resistance (unvulcanized rubber can be easily peeled off from each other, the index is ◎) Peel resistance is over 1N / cm and less than 2N / cm: Good adhesion prevention (unvulcanized rubber can be peeled off from each other without load, index is ○) Peel resistance is between 2N / cm and 3N / cm: poor adhesion resistance (the load when peeling unvulcanized rubber from each other is large, adhesion resistance is low, and the index is △) Peel resistance exceeds 3N / cm: Very poor adhesion resistance (rubbers are in close contact with each other and are difficult to peel off. Very poor adhesion resistance, index is ×)
[0046] [Dispersibility] An aqueous dispersion of the anti-adhesive composition for unvulcanized rubber (water weight ratio: 98.5 wt%) was prepared, placed in a 100 ml graduated cylinder and allowed to stand for 24 hours. After standing, the presence or absence of precipitation was confirmed. If precipitation was present, the graduated cylinder was inverted and mixed to evaluate whether the precipitation was redispersed. The evaluation criteria for dispersibility were as follows. No precipitation: Dispersibility is very good (index is ◎) Sedimentation occurs, but it is easily redispersed: Dispersibility is good (number of inversions is within 5 times, index is ○) Settling occurs and redispersion is difficult: poor dispersibility (number of inversions exceeds 5 times but is within 10 times, the index is △) Settling occurs and redispersion is very difficult: Dispersibility is very poor (number of inversions exceeds 10, index is ×)
[0047] Example 1 80 g of bentonite 1, 10 g of calcium carbonate, 8 g of sodium dioctyl sulfosuccinate, and 2 g of POE(3) tridecyl ether were uniformly mixed to obtain an anti-adhesive composition for unvulcanized rubber. Next, 4.5 g of the above anti-adhesive composition was added to 295.5 g of tap water and uniformly dispersed in the water to obtain an aqueous dispersion of an anti-adhesive composition for unvulcanized rubber. The obtained aqueous dispersion was used to evaluate the anti-adhesive properties and dispersibility. The evaluation results are shown in Table 1, and the anti-adhesive properties and dispersibility were excellent.
[0048] (Examples 2 to 23) In Examples 2 to 23, anti-adhesive compositions for unvulcanized rubber and aqueous dispersions thereof were obtained and evaluated in the same manner as in Example 1, except that the compositions were changed as shown in Tables 1 to 3. The evaluation results are shown in Tables 1 to 3.
[0049] Comparative Example 1 80 g of bentonite 4, 10 g of calcium carbonate, 8 g of sodium dioctyl sulfosuccinate, and 2 g of POE(3) tridecyl ether were uniformly mixed to obtain an anti-adhesive composition for unvulcanized rubber. Next, 4.5 g of the above anti-adhesive composition was added to 295.5 g of tap water and uniformly dispersed in the water to obtain an aqueous dispersion of an anti-adhesive composition for unvulcanized rubber. The obtained aqueous dispersion was used to evaluate the anti-adhesive properties and dispersibility. The evaluation results are shown in Table 4, and the dispersibility was poor.
[0050] (Comparative Examples 2 to 8) In Comparative Examples 2 to 8, anti-adhesive compositions for unvulcanized rubber and aqueous dispersions thereof were obtained and evaluated in the same manner as in Comparative Example 1, except that the compositions were changed as shown in Table 4. The results are shown in Table 4. In the above examples and comparative examples, POE(n) means polyoxyethylene (number of repeating oxyethylene units: n), and POP(n) means polyoxypropylene (number of repeating polyoxypropylene units: n). The type of iron compound contained in the silicate used and the weight ratio of the iron compound to the silicate are as follows: Bentonite 1: 1% iron oxide by weight, 99% silicate by weight Bentonite 2: 2% iron oxide and iron sulfide by weight, 98% silicate by weight Bentonite 3: 5% iron oxide and iron sulfide by weight, 95% silicate by weight Bentonite 4: 10% by weight of iron oxide and iron sulfide, 90% by weight of silicate Bentonite 5: 15% iron oxide and iron sulfide by weight, 85% silicates by weight Bentonite 6: 20% by weight of iron oxide and iron sulfide, 80% by weight of silicate Kaolin: 0.1% by weight of iron oxide, 99.9% by weight of silicate
[0051] [Table 1]
[0052] [Table 2]
[0053] [Table 3]
[0054] [Table 4]
[0055] As can be seen from Tables 1 to 3, the adhesion-preventive compositions for unvulcanized rubber of Examples 1 to 23 are adhesion-preventive compositions for unvulcanized rubber containing an inorganic component and a surfactant, the inorganic component essentially containing silicate and at least one selected from iron oxide and iron sulfide, the total weight ratio of iron oxide and iron sulfide to the total of silicate, iron oxide and iron sulfide is 10% by weight or less, the surfactant contains anionic surfactant (A) and nonionic surfactant (B), and the weight ratio (A / B), expressed as the weight of (A) / the weight of (B), is 1 to 20, and therefore the compositions have both excellent dispersibility and adhesion prevention, which is the subject of the present application. On the other hand, as can be seen from Table 4, when the total weight ratio of iron oxide and iron sulfide to the total of silicate, iron oxide, and iron sulfide exceeds 10% by weight (Comparative Examples 1 and 2), when (A / B) is not within the range of 1 to 20 (Comparative Examples 3, 4, 5, and 6), and when silicate and at least one selected from iron oxide and iron sulfide are not contained (Comparative Examples 7 and 8), at least one of the issues of dispersibility and anti-adhesion properties, which are the problems of the present application, is not achieved. [Industrial Applicability]
[0056] The anti-adhesive composition for unvulcanized rubber of the present invention is used in the production and processing of unvulcanized rubber products, and can prevent adhesion of rubber when the unvulcanized rubber is stored in a pile until it is transferred to the next process such as molding, vulcanization, etc. In this case, the composition has good dispersibility and anti-adhesiveness, making it possible to reduce defects in rubber products.
Claims
1. An anti-adhesive composition for unvulcanized rubber, comprising an inorganic component and a surfactant, The inorganic component essentially contains a silicate and at least one selected from iron oxide and iron sulfide, a total weight ratio of the iron oxide and the iron sulfide to the total weight of the silicate, the iron oxide, and the iron sulfide is 2 to 10% by weight, The surfactant comprises an anionic surfactant (A) and a nonionic surfactant (B), and the weight ratio (A / B) expressed as the weight of (A) / the weight of (B) is 1 to 20.
2. 2. The adhesion preventive composition for unvulcanized rubber according to claim 1, further comprising a carbonate and / or a metal soap, and the total content of the carbonate and the metal soap is 1 to 40 parts by weight per 100 parts by weight of the total amount of the inorganic component and the surfactant.
3. 3. The adhesion inhibitor composition for unvulcanized rubber according to claim 1, wherein the anionic surfactant (A) comprises a fatty acid soap.
4. A method for producing adhesion-preventively treated unvulcanized rubber, comprising a treatment step of adhering the adhesion-preventive composition for unvulcanized rubber according to any one of claims 1 to 3 to a surface of molded unvulcanized rubber.
Citation Information
Patent Citations
JP1974018780A
Sticking-preventing agent for unvulcanized rubber
JP2011144221A
Adhesion-preventive agent for unvulcanized rubber, and method for producing adhesion prevention-treated unvulcanized rubber
JP2013213202A
Adhesion prevention agent for unvulcanized rubber and its utilization
JP2017031296A
Adhesion preventive agent composition for unvulcanized rubber and use of the same
JP2018100387A
